Emergency Medical Services and Stroke Management: A Review of Current Guidelines and Practices - Alsamhari, Abdullah; Gilkaramenthi, Rafiulla; Alamer, Bader Hussain; M. Mushawwah, Saad; Abdulbari, Hamdi Hasan; Altaezi, Lara; Jebreel, Albaraa (Utan Kayu Publishing, 2025)
The worldwide occurrence of strokes reaches around 15 million cases per year while these conditions persist in more than 100 million patients at once. Worldwide stroke stands as the second main cause of mortalities since 88% of all stroke deaths occur within low- and middle-income countries (LMICs). Emergency Medical Services establish critical intervention paths because they detect strokes early while providing immediate on-scene treatment and quick response times that directly affect patient recovery. The effectiveness of proposed quality indicators to improve prehospital stroke treatment remains unknown independently from other indicators. The research tackles the developing EMS functions in stroke management through an analysis which shows how prehospital triage tools together with telehealth integration and mobile stroke services shorten the door-to-needle period and improve patient treatment results. The potential of point-of-care diagnostic tools for stroke subtype identification gets investigated to identify their contribution to optimizing prehospital decision-making processes. The text examines crucial issues within prehospital stroke care such as restricted EMS service accessibility and minimal training support and inadequate evidence-based protocol data. The reduction of stroke mortality and improvement of patient recovery requires future research to focus on EMS collaboration with multilevel stakeholders through technology innovation and policy equality to optimize stroke management in underserved healthcare environments.